ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI YIELD OBLIGASI NEGARA TAHUN 2010 - 2012 - Anang Aulia Rahman; sam'ani - (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2013)
This research examines the effect of term to maturity, inflation, interest rate (BI rate), exchange rate and oil price to bond yield. How far which all that variable will influence the yield of bond discussed through in this research. Market interest rate reference in this research is BI rate, term to maturity is residual lifetime of bond (maturity date), exchange rate is Rupiah median rate to US Dollar, inflation is inflation rate per year and oil price universalize.The results show correlation between bond yield with term to maturity, inflation, interest rate,  exchange  rate  and  oil  price  are  0,925.  While  coefficient  determination  (Adjusted  R Square) equal to 0,854, its meaning 85,4% of bond yield explainable by term to maturity, inflation, interest rate, exchange rate and oil price, the rest (14,6%) explained by others factor. By multiple regression stepwise method, we know that term to maturity (sig 0,000), inflation (sig 0,000), exchange rate (sig 0,001) and oil price (sig 0,000) have significant effect to bond yield. But interest rate (sig 0,331) has not a significant to bond yield. Keyword : Bond yield, term to maturity, inflation, BI Rate, exchange rate and oil price